The Use of Halal Labels to Improve the Consumer Loyalty of Cosmetic Products in Bandung City Indonesia - Maya Dora, Yenny; Faritzal, Adam (International Journal of Psychosocial Rehabilitation, 2020)
The majority of the population in Indonesia is Muslim. It makes the companies produce their products with halal labels on them. It is done to make the products accepted in the market. The use of halal labels among producers in Indonesia is a must. This study aims to analyze how the influence of the use of halal labels by cosmetic products in Bandung city on customer loyalty. The sample of this study was 300 female cosmetic users in Bandung city. The approach is using SEM AMOS. The results of this study prove that the form of loyalty, or customer loyalty, is more dominantly formed by trust, while the halal labels only reinforce it. The results of this study are different from previous studies, which stated that halal labels dominantly form customer loyalty. The implications of this study can be used by entrepreneurs in cosmetics, food, beverages, clothing, and medicine.